2013
DOI: 10.1021/jf400353h
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Key Aroma Compounds in Raw (Unheated) and Heated Japanese Soy Sauce

Abstract: An investigation using the aroma extract dilution analysis (AEDA) technique of the aroma concentrate from a raw Japanese soy sauce and the heated soy sauce revealed 40 key aroma compounds including 7 newly identified compounds. Among them, 5(or 2)-ethyl-4-hydroxy-2(or 5)-methyl-3(2H)-furanone and 3-hydroxy-4,5-dimethyl-2(5H)-furanone exhibited the highest flavor dilution (FD) factor of 2048, followed by 3-(methylthio)propanal, 4-ethyl-2-methoxyphenol, and 4-hydroxy-2,5-dimethyl-3(2H)-furanone having FD factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 27 publications
3
72
1
Order By: Relevance
“…Benzeneacetic acid ethyl ester, a high boiling point ester, did not present in aHVP sample. This compound, being one of the major contributors to soy sauce flavor (Kaneko et al 2012(Kaneko et al , 2013, was found at low concentration in pure soy sauce sample and several soy sauce products. It is noteworthy that the amount of fatty acid ester in soy sauce depends on varieties of soybean which were used in the brewing material.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Benzeneacetic acid ethyl ester, a high boiling point ester, did not present in aHVP sample. This compound, being one of the major contributors to soy sauce flavor (Kaneko et al 2012(Kaneko et al , 2013, was found at low concentration in pure soy sauce sample and several soy sauce products. It is noteworthy that the amount of fatty acid ester in soy sauce depends on varieties of soybean which were used in the brewing material.…”
Section: Resultsmentioning
confidence: 99%
“…Among these compounds, dozens of components were shared commonly with different amount in soy sauce products. According to the previous report (Nunomura et al 1984;Kaneko et al 2012Kaneko et al , 2013Feng et al 2015), some typical or key volatile flavor compounds, which might be the contributors to the flavor of soy sauce, were summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations